Molecular analysis of Fusarium oxysporum f. sp. cubense isolates and defense gene expression in banana infected with Fusarium wilt / Kamilatulhusna Zaidi - Kamilatulhusna , Zaidi (2019)
The Panama disease of banana, that blocks the xylem from transporting water and nutrients, is transmitted by the soil-borne fungus, Fusarium oxysporum f. sp. cubense (Foc). Knowledge of the characteristic and morphological behavior of the fungal population is crucial to develop strategies to reduce the damage by the disease. At present, there is no effective and economically safe methods are available to protect crops from Fusarium wilt disease. The identification of Fusarium species is also challenging as it relies on the slight differences in its morphology. Different cultural conditions can cause similar species to diverge. Additionally little is known about the genetic and molecular basis of the pathogenic mechanism of interaction between Foc and banana. A reliable greenhouse bioassay is therefore needed to help gain deeper insight on Foc-banana interactions. A standardized bioassay is an essential pre-requisite for biological control studies and epidemiology research. On top of that, progressive increase of invasive outbreaks and reports of Fusarium species further emphasize the necessity for a rapid, practical and reproducible bioassay protocol. Inoculum standardization is an important parameter in such procedures as optimal desired concentration and reproducibility of spore suspension may influence the bioassay results. This study focused firstly on the morphology, physiology and the pathogenic effects of Foc available in our collection. We aimed to study the variability of the pathogen’s phenotypic characteristic with its pathogenicity towards the host. Additionally we also developed a fast and precise method of evaluating the cell-density of Fusarium spore suspension in a cv. ‘Berangan’ bioassay experiment. We then described a simple standardized workflow and procedures for testing Fusarium wilt disease response in Musa acuminata using cv. ‘Berangan’ of tissue-culture origin as a model. In our experiment, we found that desired spore concentration of 1 x 104 to 106 were obtained after 7 day-incubation in the dark at 26°C to 28°C with two times of shaking per day. These optimised conditions are proposed as guidelines for a reference inoculum preparation method in subsequent bioassay experiments. Interestingly, during infection of Berangan with Foc using root-immersed approaches, phenotypic assays were able to detect physical symptoms as early as 2 days post-inoculation and molecular detection was able to detect differences in gene expression as early as 2 hours post infection in a standardized challenge assay. Berangan was found to be highly susceptible to FocR4 (C1 HIR isolate) with LSI and RDI scores of 3.74 and 4.39 respectively. The molecular approach detected differential expression of pathogen related protein 10 (PR10) and phenylalanine ammonia lyase (PAL) genes that showed a measureable transcript of RNA at day 0 followed by signature changes as early as day 2 and day 4. We also describe a procedure for extracting good quality RNA from healthy and infected banana plantlets for RT-qPCR analysis. RPS2 was validated as the most stable reference genes for normalization of defense-related genes in RT-qPCR. The analyses results showed that, the expressions of PR10 and PAL genes were upregulated upon infection by Foc, which indicated the activation of defense responses in the banana-Foc interaction.